BIOLOGICAL EVENTS USING A RECURRENT NEURAL NETWORK - Minakshi Kumari (International Journal of Multidisciplinary Research and Studies, 2020)
The computing power that is recurrent neural networks can be explored Let's look specifically at one learning strategy that can be applied to any method of training. We designed a prediction model to determine and classify a variety of biological events that can be triggered by certain phrases. We investigate the architecture of deep neural networks and propose an attention mechanism that can learn to value words differently depending on the context in which they are found. At the top layer of the network, we found that adding a set of features that were both simple and efficient was quite beneficial. It is impossible to overlook the impact that domain-based candidate filtering can have on overall performance because it plays such an important role in reducing the number of false positives. A new aspect of our architectural design is the interplay between multiple layers and components, such as the focus layer, the stacked balsam, and the feed-forward layers, which is necessary to generate an accurate model.